THE IMPORTANCE OF PSYCHOLOGICAL TRAINING IN THE SPIRITUAL DEVELOPMENT OF STUDENTS (Western European Journal of Historical Events and Social Science, 2024)
This article discusses the essence of social psychological training and its role in human life.